2006
DOI: 10.1002/jcp.20852
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin polarizes Th1/Th2 immune responses through the inhibition of immunostimulatory function of dendritic cells

Abstract: Silibinin is the primary active compound in silymarin. It has been demonstrated to exert anti-carcinogenic effects and hepato-protective effects. However, the effects of silibinin on the maturation and immunostimulatory activities exhibited by dendritic cells (DCs) remain, for the most part, unknown. In this study, we have attempted to determine whether silibinin can influence surface molecule expression, dextran uptake, cytokine production, capacity to induce T-cell differentiation, and the signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 50 publications
(47 reference statements)
1
29
0
1
Order By: Relevance
“…Silibinin can suppress the expression of inflammatory genes such as CD80 and MHC class I and inhibit the lipopolysaccharide (LPS)-induced activation of mitogen-activated protein (MAP) kinases (important in vascular gene regulation) and the nuclear translocation of the NF-kB p65 subunit in murine dendritic cells [101]. Tangeretin and nobiletin, polymethylated flavonoids from citrus peel, inhibit IL-1b-induced COX-2 expression in human lung carcinoma cells [102].…”
Section: In Vitro Studies Of Pps and Inflammationmentioning
confidence: 99%
“…Silibinin can suppress the expression of inflammatory genes such as CD80 and MHC class I and inhibit the lipopolysaccharide (LPS)-induced activation of mitogen-activated protein (MAP) kinases (important in vascular gene regulation) and the nuclear translocation of the NF-kB p65 subunit in murine dendritic cells [101]. Tangeretin and nobiletin, polymethylated flavonoids from citrus peel, inhibit IL-1b-induced COX-2 expression in human lung carcinoma cells [102].…”
Section: In Vitro Studies Of Pps and Inflammationmentioning
confidence: 99%
“…We reported previously that a variety of phytochemicals exhibit profound immunoregulatory activity, particularly in DC [8][9][10][11]. D-pinitol (3-O-methyl-chiroinositol), an active principle of the traditional antidiabetic plant, Bougainvillea spectabilis, reportedly exerts insulin-like effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…The immunomodulatory activity of quercetin has been investigated in NK cells (17), macrophages (18), mast cells (19), neutrophils (20), B cells (21), and T cells (22). Although a number of studies have reported the activity of flavonoids in the modulation of DC activation (23)(24)(25)(26)(27), the effect of quercetin on DCs remains unknown. In this study, we examined the immunomodulatory effect of quercetin on DC activation.…”
mentioning
confidence: 99%